PENGARUH PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE PADAMATERI SISTEM PENCERNAAN MANUSIA TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VIII SMP NEGERI 1 KEPENUHAN HULU TAHUN PEMBELAJARAN 2014/2015 - Bakri, Maria; Lestari, Rena; Ade, Filza Yulina (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The aim of the study was to determine the effect of cooperative learning type of Think Pair Share toward biological studentâs learning result on the human digestive system at grade VIII of SMP Negeri 1 Kepenuhan hulu for academic years on 2014/2015. The method was quasi experiment with Control Group Pretes-Posttest Design type. The sample was taken by using Purposive sampling. The sample was students as experiment class at grade VIIIA and students as a control class at grade VIII B. The instrument of the study was the test. The data analysis used t-test, and obtained ttest = 3,74 of significant 0,05 that ttable = 2,03 , so it can be concluded that by t-test> t-table means that alternative hypothesis was accepted